African Migration Narratives : Politics, Race, and Space - Taylor, Jack, 1982-; Iheka, Cajetan Nwabueze (Rochester studies in African history and the diaspora., 2020)
This essay collection examines the representations of migration in African literature, film, and other visual media. Inspired by the proliferation of texts focused on this theme and the ongoing migration crises, essays in the volume probe the ways in which African cultural productions shape and are shaped by the migration debates, the contributions these productions make to an understanding of globalization, and the stylistic features of the works. The texts analyzed here include important recent writings and films that have yet to receive considerable scholarly attention, by artists such as Chimamanda Adichie, Teju Cole, Leila Aboulela, Noo Saro-Wiwa, and Marzek Allouache. Current scholarship on migration largely focuses on the journey from Third World spaces to the First World, thereby radically limiting our understanding of migratory flows. This project works against this lopsided analysis of migration and considers narratives of return as central to migratory flows. The book also invests in underanalyzed and underrepresented diasporas on the continent including the Lusophone and Indian diasporas. Unlike much scholarship on migration in African cultural studies, which tends to focus primarily on a genre (literature), a region, or a specific language, the current book emphasizes Africa's geographical and linguistic diversity by being attentive to Anglophone, Francophone, and Lusophone areas, as well as an array of texts encompassing various genres.